Dynamics of Mental Workload and Occupational Stress in the High-Risk Public Healthcare Sector: A Systematic Literature Review - Noufal Evan Septyan; Husaini Husaini; Rizqi Puteri Mahyudin; Lenie Marlinae; Mohamad Isa (GLOBAL HEALTH SCIENCE GROUP, 2026)
Mental health issues in the workplace are a fundamental priority in healthcare systems, particularly in high-risk environments characterized by complex operational demands and acute time pressures. Increased cognitive load, when exceeding individual thresholds, has consistently been identified as a major catalyst for work-related stress, which subsequently impairs the clinical performance of healthcare practitioner. This research is designed to rigorously evaluate the correlation between mental workload quantified through the NASA Task Load Index (NASA-TLX) instrument and job stress manifestations, anchored in the conceptual framework established by the National Institute for Occupational Safety and Health (NIOSH). The investigation focuses on high-risk public healthcare sectors to map the underlying psychosocial dynamics affecting the workforce. The synthesis of findings demonstrates a significant and positive correlation between mental workload and professional stress. Specifically, the dimensions of mental demand, temporal demand, and effort emerged as the predominant predictors of psychological strain. Furthermore, the analysis indicates that organizational variables, notably social support and job control, function as critical moderating factors that either attenuate or exacerbate the intensity of the relationship between cognitive demands and perceived stress. The study concludes that mental workload is a pivotal determinant of job stress among healthcare professionals within high-risk public service domains. Consequently, there is an imperative for interventions rooted in cognitive ergonomics and the reinforcement of organizational support systems. Such proactive measures are vital to mitigate psychosocial risks and sustain the overarching quality of healthcare delivery.